Differences of Weighted Composition Operators on Hα∞(BN)∗. (29th December 2009) - Dai, Jineng; Ouyang, Caiheng
Abstract : We study the boundedness and compactness of differences of weighted composition operators on weighted Banach spaces in the unit ball ofC N .